PILOMYXOID ASTROCYTOMA PRESENTING AS DIENCEPHALIC SYNDROME - Khan, Amjad Ali; El-Borai, Ahmed Kamal (Journal of Ayub Medical College Abbottabad, 2014)
We report the case of a child who presented with diencephalic syndrome. During diagnostic work-up, he was found to have a supra-sellar hypothalamic tumour. Histopathological examination of the tumour revealed it to be pilomyxoid astrocytoma, which is a WHO grade-II tumour, previously considered to be part of the spectrum of WHO grade-I pilocytic astrocytomas. However, because of its characteristic histopathology and behaviour, it was later segregated from pilocytic astrocytomas. In this case report, we discuss the cytological and histopathological features of this tumor with the aim of increasing awareness of this tumour amongst general histopathologists, to highlight the importance of its differentiation from pilocytic astrocytomas in view of its different behaviour, treatment and prognosis and that it should be included in the differential diagnosis of diencephalic syndrome. Keywords: Diencephalic syndrome, Pilocytic astrocytomas, supra-sellar hypothalamic tumour, pilocytic astrocytoma